2003
DOI: 10.1108/00346650310507082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of selected essential and non‐essential metals in various canned and raw foodstuffs consumed in Pakistan

Abstract: Levels of selected essential metals (Cu, Fe and Zn) and non‐essential metals (Cd and Pb) were determined by the wet digestion based atomic absorption flame spectrophotometric method in twenty canned foodstuffs of local and foreign origin. The study revealed that on average, the concentrations of Fe, Cd and Pb in local foodstuff were more than those found in imported canned products. The contents of Fe and Pb in local canned food were almost double that of the counterpart imported versions. Analysis of the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…They are stable elements and persist for long periods in the environment. There is evidence to suggest that the levels of As and Cd in mussels are decreased by processing or freezing, Devesa et al ( 2008 ) , Dahl et al ( 2010 ) and Metian et al ( 2009 ) , and Cd and Pb are increased by canned storage, Waheed et al ( 2003 ) . However, for example, methyl mercury, Me-Hg, can be found in canned fi sh that has undergone severe thermal treatment, Lawley et al ( 2008 ) .…”
Section: Pollutant Trace Elementsmentioning
confidence: 99%
“…They are stable elements and persist for long periods in the environment. There is evidence to suggest that the levels of As and Cd in mussels are decreased by processing or freezing, Devesa et al ( 2008 ) , Dahl et al ( 2010 ) and Metian et al ( 2009 ) , and Cd and Pb are increased by canned storage, Waheed et al ( 2003 ) . However, for example, methyl mercury, Me-Hg, can be found in canned fi sh that has undergone severe thermal treatment, Lawley et al ( 2008 ) .…”
Section: Pollutant Trace Elementsmentioning
confidence: 99%
“…Although the concentrations and incidences of heavy metals in canned tomato paste have been assessed in other parts of the world, no complementary study exists in Ghana (Al-Khalifa 1997;Tu¨rker and Yu¨ksel 1997;Waheed et al 2003;David et al 2008;Melaku 2009;Itodo and Itodo 2010). Estimation of heavy metal levels in canned tomato in Ghana will determine whether this dietary exposure is within the safe regulatory exposure limits.…”
Section: Introductionmentioning
confidence: 97%
“…Canned food may present considerable concentrations of Cu, Mn, and Zn, so that their dietary intake may constitute an important source [46]. A Pakistan study revealed that the concentrations of Cd, Fe, and Pb in local canned foodstuff were higher than those found in imported canned products [47]. The contents of Fe and Pb in local canned food were almost double that of the counterpart imported versions [47].…”
Section: Trace Elements and Dietmentioning
confidence: 99%
“…A Pakistan study revealed that the concentrations of Cd, Fe, and Pb in local canned foodstuff were higher than those found in imported canned products [47]. The contents of Fe and Pb in local canned food were almost double that of the counterpart imported versions [47]. Tinplate is widely used in food industry as a robust form of packaging.…”
Section: Trace Elements and Dietmentioning
confidence: 99%